2013
DOI: 10.1002/cbin.10093
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Cofilin‐1 blocks PDGF‐induced proliferation in eutopic endometrium of endometriosis patients

Abstract: Platelet-derived growth factor (PDGF) is well known to induce proliferation in variety of cells. The aim of this study was to investigate whether there is a correlation between the expression of Cofilin-1 (CFL1) and the proliferation of eutopic endometrium stromal cells (ESC) in response to PDGF stimulation. Results show that PDGF induced the expression of CFL1 in ESC and promoted proliferation of ESC significantly in a time- or dose-dependent manner. After silencing CFL1, the effect of PDGF on promoting ESC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…A number of studies have indicated that factors regulating actin cytoskeleton, can exert regulatory functions on cell proliferation. For example, Cofilin phosphorylation mediates proliferation in response to platelet-derived growth factor (PDGF) in rat aortic smooth muscle cells (Won et al, 2008), and inhibition of Cofilin-1 expression blocks PDGFinduced proliferation in endometrium (Wang et al, 2013). Conversely, ectopic-expression of of ADFs and Cofilin suppress the motility and proliferation of human lung cancer cells (Lee et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies have indicated that factors regulating actin cytoskeleton, can exert regulatory functions on cell proliferation. For example, Cofilin phosphorylation mediates proliferation in response to platelet-derived growth factor (PDGF) in rat aortic smooth muscle cells (Won et al, 2008), and inhibition of Cofilin-1 expression blocks PDGFinduced proliferation in endometrium (Wang et al, 2013). Conversely, ectopic-expression of of ADFs and Cofilin suppress the motility and proliferation of human lung cancer cells (Lee et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…PDGF to dobrze znany czynnik odpowiedzialny za indukcję proliferacji wielu rodzajów komórek (32) . Syntetyzowany jest nie tylko przez płytki krwi, lecz także przez komórki endotelialne, fibroblasty czy komórki mięśni gładkich.…”
Section: Płytkopochodny Czynnik Wzrostu (Pdgf)unclassified
“…PDGF is a well-known factor responsible for inducing proliferation of many types of cells (32) . It is synthesized not only by blood platelets but also by endothelial cells, fibroblasts and smooth muscle cells.…”
Section: Platelet-derived Growth Factor (Pdgf)mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Peng et al [10] suggested that the expression of GATA-3 in endometrial epithelial cells of women with endometriosis was higher than that of healthy women. Specially, it has been proposed that number of proliferating endothelial cells increase in the endometrium of endometriosis patients [11,12], which implies that the proliferation of endometrial cells is important in the patho-genesis of endometriosis. However, to our knowledge, the role of GATA-3 in the proliferation of endometrial cells has not been investigated.…”
Section: Introductionmentioning
confidence: 99%